Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1039/d1qm00023c
|View full text |Cite
|
Sign up to set email alerts
|

Full-type photoluminescence from a single organic molecule for multi-signal temperature sensing

Abstract: Full-type photoluminescence including concomitant fluorescence, delayed fluorescence, and room-temperature phosphorescence from a single organic molecule is used for multi-signal temperature sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…The triplet excitons are especially sensitive to temperature and molecular oxygen, [ 32 ] and the phosphorescence quenching caused by molecular oxygen is one of the main nonradiative decay processes. Furthermore, it was found that the energy transfer from the lowest excited triplet state (T 1 ) of the phosphor to triplet oxygen can produce singlet oxygen that is highly reactive and can participate in exclusive chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The triplet excitons are especially sensitive to temperature and molecular oxygen, [ 32 ] and the phosphorescence quenching caused by molecular oxygen is one of the main nonradiative decay processes. Furthermore, it was found that the energy transfer from the lowest excited triplet state (T 1 ) of the phosphor to triplet oxygen can produce singlet oxygen that is highly reactive and can participate in exclusive chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-free room-temperature phosphorescent (RTP) materials with unique advantages of low cost, negligible toxicity, and easy synthesis have attracted more and more attention in recent years due to their potential applications in anti-counterfeiting, encryption, optical sensing, bioimaging, and electroluminescence. To realize efficient RTP emission, it is necessary not only to enhance the intersystem crossing (ISC) process to improve triplet exciton formation but also to suppress the non-radiative decay of triplet excitons. Until now, most highly efficient RTP materials are based on small molecular crystals, which can form rigid microenvironments to suppress non-radiative decay. However, stringent preparation conditions and poor film-forming properties of these molecular crystals may restrict their real applications as RTP films.…”
Section: Introductionmentioning
confidence: 99%
“…The research of organic luminescent materials has drawn great attention, because of their wide applications in bio-imaging, sensors, anti-counterfeiting and displays, etc. [1][2][3][4][5][6][7] With different luminescence properties, luminogens generally present different photophysical processes and applicable scenarios. For instance, thermally-activated delayed fluorescence (TADF) indicates a radiative transition of singlet excitons after undergoing intersystem crossing (ISC) and reverse intersystem crossing (RISC) between excited singlet and triplet states.…”
Section: Introductionmentioning
confidence: 99%